2010
DOI: 10.2139/ssrn.1817292
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Natural Disasters and Economic Growth

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
411
1
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(443 citation statements)
references
References 16 publications
18
411
1
13
Order By: Relevance
“…Next, I follow Cavallo et al () and aggregate the country‐specific treatment effects into four groups based on income classification of the country during the year of VAT adoption. I normalize the estimates before aggregating them by setting the GDP per worker of each treated country equal to one in the treatment year.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Next, I follow Cavallo et al () and aggregate the country‐specific treatment effects into four groups based on income classification of the country during the year of VAT adoption. I normalize the estimates before aggregating them by setting the GDP per worker of each treated country equal to one in the treatment year.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Fourth, the results of this study can also contribute to the literature on the long‐term economic impacts of natural disasters, which has yielded mixed findings. Skidmore and Toya () found no negative effect from natural disasters on long‐term growth, whereas Cavallo et al (), duPont IV and Noy (), and Noy and Nualsri () found a persistent negative effect. Xiao () found a negligible effect from a flood in the United States on income in the long term but a long‐lasting negative effect on agricultural output.…”
Section: Introductionmentioning
confidence: 97%
“…We now formally examine the mechanism of the observed spatial reorganization in the affected area by controlling for a body of confounding factors. To construct a credible control group, we adopt the SC method to test the impact of the earthquake using a comparative analysis, which was developed by Abadie and Gardeazabal () and Abadie, Diamond, and Hainmueller (), and later adopted by a stream of empirical studies, such as Cavallo, Galiani, Noy, and Pantano (), Barone and Mocetti (), and Ando (). The approach aims to construct an SC unit of a treated unit using the weighted average of a set of untreated donor units, after which the outcomes of the treated and the SC units are compared with evaluate the impact of the treatment.…”
Section: Empirical Strategy: the Sc Methodsmentioning
confidence: 99%